Validasi LKS fisika bermuatan literasi saintifik pada materi fluida - Efni Zalpita; hidayati hidayati; renol afrizon (PILLAR OF PHYSICS EDUCATION, 2020)
This research intends to produce a worksheet containing scientific literacy on static fluid and dynamic fluid that has been valid tested. The use of worksheets can support the physics learning process. One solution is a worksheet with scientific literacy with static fluid and dynamic fluid. The worksheets presented in this worksheet already use scientific literacy steps. There are three scientific literacy steps, namely the scientific context, the scientific process and the scientific concept. This research is a type of research and development (R&D) that uses Sugiyono's development model. Sugiyono's development model has ten phases. This research uses only five phases, namely potential and problems, data collection, product design, design validation, and the design revision phase. To test the validity, this study used a questionnaire instrument. Valid questionnaire instruments were filled by three lecturers of Physics majors from FMIPA UNP as validators. Final data from the questionnaire instrument were analyzed using descriptive statistics. From the validity test, the worksheets developed were considered to be very valid with an average percentage score of 85.95%. thus, the Physics student worksheets with scientific literacy are in a very good category so that is suitable for use in the physics learning process.